2017
DOI: 10.1002/brb3.683
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of functional magnetic resonance imaging studies of eye movements and visual word reading

Abstract: IntroductionThe pattern of eye movements during reading is substantially correlated with linguistic factors. While there have been a large number of studies on the neural mechanisms of eye movements and word reading separately, a limited number of studies have compared the activation patterns of these two processes and discussed the associations of their corresponding brain regions within the framework of naturalistic reading.MethodsThis study conducted a meta‐analysis of the existing functional magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…However, in a study by Jobard et al (2007), the authors directly contrast reading text to listening to speech and report activation in the left precentral gyrus and superior parietal lobe, regions within the DAN, as well as bilateral occipital regions, thus suggesting that the DAN engages during reading rather than auditory presentation of language. A recent meta-analysis of word reading and eye movements during fMRI support this notion, demonstrating overlapping activation for reading and eye movements in left superior parietal and precentral regions (Zhou & Shu, 2017). It is possible that the recruitment of the DAN in this study reflects the use of visually presented text and increased use of this network during aging is used to help maintain and orient visual attention to the text.…”
Section: Discussionmentioning
confidence: 92%
“…However, in a study by Jobard et al (2007), the authors directly contrast reading text to listening to speech and report activation in the left precentral gyrus and superior parietal lobe, regions within the DAN, as well as bilateral occipital regions, thus suggesting that the DAN engages during reading rather than auditory presentation of language. A recent meta-analysis of word reading and eye movements during fMRI support this notion, demonstrating overlapping activation for reading and eye movements in left superior parietal and precentral regions (Zhou & Shu, 2017). It is possible that the recruitment of the DAN in this study reflects the use of visually presented text and increased use of this network during aging is used to help maintain and orient visual attention to the text.…”
Section: Discussionmentioning
confidence: 92%
“…Left PCun has been implicated in orthographic representation [83] and monitoring the orthographic and phonological consistency related to attention [84], however, it is also has been suggested to associate with semantic representation [85]. A large amount of studies have suggested that left MFG is also associated with semantic representation (for a review see [77]), in addition to allocation spatial attention during word recognition [86], but it is not strongly associated with orthographic representation. It is possible that our finding of repetition enhancement in left PCun and left MFG is related to the co-activation of semantic representations of the embedded words, consistent with the view that sub-word orthographic interference is strong enough to connect with meaning and induce semantic interference [20, 87].…”
Section: Discussionmentioning
confidence: 99%
“…The four active TMS sites were localized by means of stereotaxic navigation on individual estimated MRIs obtained through a 3D warping procedure fitting a high-resolution MRI template with the participant's scalp model and craniometric points (Softaxic, EMS). Neuro-navigation used anatomical Talairach coordinates (Talairach and Tournoux, 1988) obtained by converting the MNI coordinates of the sites of interest from a recent meta-analysis of fMRI studies of eye movements (Zhou and Shu, 2017). Coordinates were x ϭ Ϫ36, y ϭ Ϫ1, z ϭ 48 and x ϭ 36 y ϭ Ϫ1, z ϭ 48 for left and right FEF, respectively, and x ϭ Ϫ30, y ϭ Ϫ53, z ϭ 49 and x ϭ 30, y ϭ Ϫ53, z ϭ 49 for left and right IPS, respectively (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…An additional analysis was performed to assess whether the chosen coordinates for the FEF stimulation site were optimal with respect to the putative cortical location of FEF at the level of individual participants. Here, coordinates for the FEF site were derived from the existing literature (Zhou and Shu, 2017). However, it is also known that the distance between FEF and M1 is ϳ2 cm in humans (Müri et al, 1991;Ro et al, 1999).…”
Section: Effect Of Tms On Visual Searchmentioning
confidence: 99%